Tobacco/Isatis intercropping system improves soil quality and increase total production value - Wang, Zhongyan; Guo, Xiaomeng; Cao, Shoutao; Yang, Mingfeng; Gao, Qiang; Zong, Hao; Shang, Xianchao; Gao, Yun; Zhang, Li; Yang, Long; Zhang, Miao; Sun, Mingming; et al. (Frontiers in Plant Science, 2024)
Continuous tobacco monocropping has caused soil degradation and yield reduction in China.Intercropping, as a specific and efficient cropping pattern, is highly associated with the enhancement of soil quality and land-use efficiency. Tobacco (Nicotiana tabacum L.)-Isatis (Isatis tinctoria L.) intercropping can significantly alleviate pests and diseases, and improve soil potential and fertility in tobacco fields. In this study, comparative analysis of three different tobacco-Isatis intercropping (B2, B3, B4) and tobacco monocropping (B1) on the soil nutrients, enzyme activities, and microbial community were conducted. B2, B3, and B4 importantly increased the contents of organic matter, available potassium, and available phosphorus content of the soil by 17.38%, 7.76%, and 2.78%, respectively. Moreover, B2 enhanced the activities of sucrase, urease, and catalase of soil by 2.35 times, 3.16 times, and 4.47 times, respectively, and B3 enhanced the activities of sucrase, urease, and catalase of soil by 2.74 times, 3.22 times, and 3.11 times, respectively. The intercropping pattern also optimized the structure of the soil microbial community. The relative abundances of Acidobacteriota, Chloroflexi, Gemmatimonadota, Planctomycetota, Nitrospirota, and Verrucomicrobiota in B3 and B4 were higher than those in B1. Positive links in soil bacterial correlation networks accounted for 47%, and soil bacteria formed a highly interactive and complex network. And compared with the B1, Ascomycota and Basidiomycota were lower abundance in B2 and B4, Ascomycota were lower abundance in B3 and Mortierellomycota were lower abundance in B2 and B3. Compared with monocropping, the chemical composition of tobacco leaves was harmoniously improved and the total production value of tobacco fields was significantly higher. The content of reducing sugar, total sugar, nicotine, potassium, and two-sugar ratio of leaves were increased after intercropping. The proportion of top-grade tobacco leaves after roasting in B2, B3, and B4 treatments were increased by 8.19%, 16.74%, and 27.32 %, respectively. The study constructs insights into microbial community interactions at in tobacco/Isatis intercropping systems, and may facilitate the further development of tobacco/Isatis intercropping systems.